Guy Debord'un "Gösteri Toplumu" Adlı Çalışması Bağlamında Mekân ve Modanın Tüketim Unsuru Olarak İncelenmesi / The Examination of Space and Fashion as a Component of Consumption in the Context of "Society of Spectacles" of Guy Debord - Kaya, Sevde (Journal of History Culture and Art Research, 2017)
Abstract Since the occurance of the concept of consumption, it has been discussed by a number of theorists. In these works, the concept of consumption has been analyzed in many different ways. Even though the consumption concept is a very financial issue, the social scientists have done some studies about consumption. In this work, I will examine the consumption perception of Guy Debord who is an influential figure for several future studies and who is a preminent actor among other consumption theorists. Debord states that the consumption is imposed to individuals via virtual reality and it is presented to the daily lives of individuals in a very pragmatic way. Debord calls the communities in which people give priority to consumption upon arranging the social relations as ‘society of spectacles’. Debord relates the concept of spectacle to the consumption. He suggests that spectacle manipulates the daily life and increases the will to consume and passivates individuals. The concept of spectacle has grown with the emergence of the leisure time and has been directed to daily pratic after the places were related to consumption. In this work, the relation between spectacle and consumption that Debord set up is examined. In the work, it is deduced that in order to accelerate the consumption, spectacle utilizes some areas such as mass media, place and fashion. Öz Tüketim kavramı ilk ortaya çıktığı andan beri birçok kuramcı tarafından tartışılmıştır. Bu çalışmalar tüketim kavramını çok farklı yönleriyle ele almıştır. Tüketim kavramı iktisadi bir konu olsa da sosyal bilimciler de tüketim ile ilgili çalışmalar yapmıştır. Bu çalışmada tüketim kuramcıları arasında önemli bir yer tutan ve fikirleri gelecek araştırmalar için esin kaynağı olan Guy Debord’un tüketim anlayışı incelenecektir. Debord, tüketimin sanal bir gerçeklik yoluyla bireylere dayatıldığını ve bu dayatmaların son derece pratik yollarla bireylerin gündelik hayatlarına sunulduğunu ifade etmektedir. Debord bireylerin pasifleştiği ve tüketimin toplumsal ilişkileri düzenlemede temel etken olduğu toplumlara “gösteri toplumu” adını vermiştir. Debord gösteri kavramı ile tüketim arasında ilişki kurmuştur. Gösterinin gündelik hayatı manipüle ettiğini, tüketim arzusunu arttırdığını ve bireyleri pasifleştirdiğini belirtmiştir. Gösteri kavramı boş zamanın ortaya çıkması ile filizlenmiş, mekânların tüketime eklemlenmesi ile gündelik pratiğe aktarılmıştır. Bu çalışmada, Debord’un gösteri ile tüketim arasında kurduğu ilişki incelenmiştir. Gösterinin tüketimi hızlandırmak için kitle iletişim araçları, mekân ve moda gibi alanlara başvurduğu tespit edilmiştir.